Mode of Delivery and Asthma at School Age in 9 European Birth Cohorts - Rusconi, F (2017)
Evidence on the association between mode of delivery and asthma at school age is inconclusive. We assessed the associations between specific modes of delivery and asthma in children from 9 European birth cohorts that enrolled participants between 1996 and 2006. Cohort-specific crude and adjusted risk ratios for asthma at ages 5–9 years were calculated using Poisson regression models and pooled. A sensitivity analysis was carried out in children born at term to reduce confounding due to perinatal factors. The study included 67,613 participants. Cohortspecific rates of cesarean delivery varied from 9.4% to 37.5%. Cesarean delivery, as opposed to vaginal delivery, was associated with an increased risk of asthma (adjusted risk ratio (aRR) = 1.22, 95% confidence interval (CI): 1.02, 1.46). Compared with spontaneous vaginal delivery, the adjusted risk ratio was 1.33 (95% CI: 1.02, 1.75) for elective cesarean delivery, 1.07 (95% CI: 0.94, 1.22) for emergency cesarean delivery, and 0.97 (95% CI: 0.84, 1.12) for operative vaginal delivery. In children born at term, the associations were strengthened only for elective cesarean delivery (aRR = 1.49, 95% CI: 1.13, 1.97). The large sample size allowed analysis of the associations between specific modes of delivery and asthma at school age. The increased risk of asthma associated with elective cesarean delivery, especially among children born at term, is relevant in counteracting the increasing use of this procedure, which is often performed without a clear medical indication.